2013
DOI: 10.1364/oe.21.013824
|View full text |Cite
|
Sign up to set email alerts
|

Light-sheet microscopy in thick media using scanned Bessel beams and two-photon fluorescence excitation

Abstract: In this study we show that it is possible to successfully combine the benefits of light-sheet microscopy, self-reconstructing Bessel beams and two-photon fluorescence excitation to improve imaging in large, scattering media such as cancer cell clusters. We achieved a nearly two-fold increase in axial image resolution and 5-10 fold increase in contrast relative to linear excitation with Bessel beams. The light-sheet penetration depth could be increased by a factor of 3-5 relative to linear excitation with Gauss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 19 publications
1
113
0
Order By: Relevance
“…Finally, alternative illumination schemes other than the Gaussian beams modeled within this study have also been reported in the literature (structured illumination, Bessel and Airy beams, multi-photon, etc.) [49][50][51][52], which may be explored using similar methodologies in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, alternative illumination schemes other than the Gaussian beams modeled within this study have also been reported in the literature (structured illumination, Bessel and Airy beams, multi-photon, etc.) [49][50][51][52], which may be explored using similar methodologies in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, quasi-Bessel beams can be generated by applying conical phase shifts to a Gaussian beam, using an axicon or a spatial light modulator. Here, a spatial light modulator is used in a configuration described by Fahrbach [14]. We implement the spatial light modulator in a separate beam path using flip mirrors to allow comparison to the original Gaussian illumination.…”
Section: Bessel Beam Illuminationmentioning
confidence: 99%
“…We have used Gaussian-beam light sheets for our imaging because of its simplicity; further improvement to the sectioning capability of the 2p excitation could be achieved by utilizing Bessel-beam light sheets [18][19][20]. Since the side lobes of Bessel beams do not contribute to useful signal generation in 2p excitation, more average laser power would be required for using Bessel-versus Gaussian-beam 2p-SPIM -care then must be exercised to ensure that the extra laser power does not inflict unacceptable photodamage to the live samples under study.…”
Section: Imaging Setup Characterizationmentioning
confidence: 99%